UMA ABORDAGEM SOBRE MATEMÁTICA FINANCEIRA E EDUCAÇÃO FINANCEIRA NO ENSINO MÉDIO - Pietras, Gelson (2014)
This work is the result of the Project “Financial Education” presented and developed in PROFMAT (UEPG), having as its corpus dates and experience in classroom collected in Colégio Sesi of Guarapuava between the years 2010 to 2014. Aiming to teach financial mathematics content, according to a requirement in the regular school, this subject was taken to classroom and these topics were used to raise students’ awareness of several subjects, such as: (a) needs to satisfy personal wishes, (b) the choice to save in the present so that the future become more fruitful, (c) rational use of the savings account, (d) dealing with debts and acquisitions, (e) investment models in short and long run, etc. To study these subjects, studies taken place in classroom and in the computer lab to take decisions in buying and selling situations as well as money administration. Besides, we approached studies shopping in cash or in installments, credit card use, strategies to pay off long run debts, the cost of a car maintenance, as well as knowledge about taxes on a worker salary and the taxes percentage for deduction in different incomes, the analyzes of houses rental and mortgage and plans to accumulate capital. The objective of these actions is to generate a change in the way of students to think about forthcoming situations in relation to their entrance in the professional life, when it is necessary to administrate the own money, so that they are prepared to take important decisions on finances.